LEGAL RECONSTRUCTION OF PHYSICAL CONSTRUCTION SERVICES BASED ON QUALITY OF PUBLIC SERVICES - suyatim suyatim (Jurnal Pembaharuan Hukum, 2017)
Construction services are useful in terms of various means to support the achievement of national development goals. Regarding the services of this construction, stipulated in Act No. 18 of 1999 and its amendments, let the rules of its implementation. However, in the implementation can not run optimally, because there are obstacles, so it requires an effort for physical development services for the public benefit can be beneficial to the community. Quality of service in the public sector is a key word to revive public confidence in the government.